Indoor positioning system for an autonomous drone - Almeida, Rafael Tavares (2019)
In robotics, the decision capabilities according to the surrounding environment evaluation are under constant evolution, subject to sudden changes, with the aim of merging the behavior of robots and humans based on sensorial data. Even though it is a complicated task, every year new solutions are built and the complexity of this task has been by-passed enabling better results that contribute to more realistic solutions. The main difficulties in the solutions developed in this area are related to the independent movement control in indoor spaces once that is necessary the use of precise positioning systems necessary for the correct localization input data to the robots ensuring the best action order as quickly as possible. The research and development process presented in this thesis is related to the need of finding an appropriate solution for the indoor positioning systems applied to an autonomous drone. However, due to the construction materials of this type of buildings, it is not possible to use systems based on global position systems (GPS). Therefore, with the conclusion of the trainee program associated with this thesis, the output is a control system for autonomous drones based on the indoor position, capable of making warehouse inventories using Radio Frequency Identification (RFID) technology. During the development process of a modular system, several solutions were considered in response to the issues and objectives of each module organized taking into account its significance for the final product. In the last project phase, it was developed a control module to support the integration of each part and also allowing the inclusion of necessary future modules.